2018
DOI: 10.1007/s00261-018-1665-2
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and diagnostic performance of hybrid PET/MRI compared with PET/CT for gynecological malignancies: a prospective pilot study

Abstract: PET/MRI is feasible and has at least comparable diagnostic ability to PET/CT for identification of primary cervical and endometrial tumors and regional metastases. PET/MRI may be superior to PET/CT for initial radiographic assessment of cervical cancers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 22 publications
1
19
0
Order By: Relevance
“…Sensitivity, specificity, and diagnostic accuracy for nodal disease were 91, 94, and 93%, respectively. The results of subsequent studies support the high diagnostic potential of hybrid PET/MRI in cervical cancer staging ( 12 , 26 28 ).…”
Section: Review Of Literaturementioning
confidence: 52%
See 1 more Smart Citation
“…Sensitivity, specificity, and diagnostic accuracy for nodal disease were 91, 94, and 93%, respectively. The results of subsequent studies support the high diagnostic potential of hybrid PET/MRI in cervical cancer staging ( 12 , 26 28 ).…”
Section: Review Of Literaturementioning
confidence: 52%
“…We have identified 26 studies consisting of a total of 801 subjects that reported on the diagnostic value of fused or integrated PET/MRI for the clinical management of female pelvic malignancies, Table 1 . Of these, 17 studies were based on an integrated PET/MRI system ( 12 18 , 26 29 , 31 34 , 36 , 37 ), and nine studies applied co-registered (fused) PET/MRI data ( 19 25 , 30 , 35 ). A total of 15 studies with 413 subjects were for staging ( 12 25 , 27 , 36 ); six studies with 187 subjects for restaging ( 31 35 , 37 ); and six studies of 175 subjects of mixed staging and restaging ( 26 30 , 36 ).…”
Section: Review Of Literaturementioning
confidence: 99%
“…Simultaneous PET/MRI images were obtained using an integrated PET/MRI scanner BiographmMR (Siemens Healthcare Sector, Erlangen, Germany) as previously reported (Schwartz et al, 2018). Patients fasted for at least 6 h before tracer injection.…”
Section: Methodsmentioning
confidence: 99%
“…In a prospective study of 18 gynecological cancer cases including cervical cancer and high-risk endometrial cancer, PET/MRI detected all primary tumors and regional lymph nodes as well as PET/CT. In addition, PET/MRI had higher sensitivity for parametrial and bladder invasion than PET/CT 19 . In another prospective study of 26 gynecological cancer cases including seven cervical cancer cases and 12 ovarian cancer cases, PET/MRI and PET/CT could equally detect regional lymph nodes metastasis 20 .…”
Section: Discussionmentioning
confidence: 91%
“…Recently, it has been reported that FDG-PET imaging combined with CT or MRI are important tools to detect the spread of many cancers. Some groups have reported the e cacy of FDG-PET examination for cervical cancer 16,[18][19][20] . In a meta-analysis, the sensitivity and speci city of PET for lymph node metastases were 74.7% (95% CI 63.3-84.0) and 97.6% (95% CI 95.4-98.9), respectively.…”
Section: Discussionmentioning
confidence: 99%